2016
DOI: 10.1166/jnn.2016.11682
|View full text |Cite
|
Sign up to set email alerts
|

Visual Screening and Colorimetric Determination of Clenbuterol and Ractopamine Using Unmodified Gold Nanoparticles as Probe

Abstract: In this paper, a sensitive method for the colorimetric detection of clenbuterol and ractopamine using citrate-stabilized gold nanoparticles (AuNPs) as probe was developed. The concentration of clenbuterol and ractopamine could be determined with naked eyes or a UV-vis spectrometer. By optimizing the influence of NaHSO₄ and incubation time, clenbuterol could be detected in the linear range of 0.1-4 µg/mL with the detection limit of 0.0158 µg/mL, and ractopamine could be detected in the linear range of 1-9 µg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Potentially interfering substances such as alanine, phenylalanine, glycerol, vitamin C, threonine, urea, exogenous cysteamine, glucose, glycine, NaCl, and CaCl 2 did not make any difference to the results. Recently, Luo et al [174] demonstrated a highly sensitive technique for direct visual detection of CLP and ractopamine in pig urine samples using AuNPs without employing any bio-recognition agent. The electrostatic interaction between AuNPs and targets (CLP or ractopamine) caused aggregation of AuNPs and produced a blue color.…”
Section: Anti-doping Detection By Plasmonic Biosensorsmentioning
confidence: 99%
“…Potentially interfering substances such as alanine, phenylalanine, glycerol, vitamin C, threonine, urea, exogenous cysteamine, glucose, glycine, NaCl, and CaCl 2 did not make any difference to the results. Recently, Luo et al [174] demonstrated a highly sensitive technique for direct visual detection of CLP and ractopamine in pig urine samples using AuNPs without employing any bio-recognition agent. The electrostatic interaction between AuNPs and targets (CLP or ractopamine) caused aggregation of AuNPs and produced a blue color.…”
Section: Anti-doping Detection By Plasmonic Biosensorsmentioning
confidence: 99%
“…5,6 The unlawful use of RAC is not confined to animals; athletes have also been observed abusing this medication. 7 As β-agonists including RAC are extremely stable and resistant to removal and decomposition from biological systems, a substantial concentration of their residues can build up in farm animals. 8 On a more serious note, accumulated RAC in the meat of animals can be partially eliminated by conventional cooking ways.…”
Section: Introductionmentioning
confidence: 99%
“…29 To date, various strategies have been used, based on changes in size, shape, and inter-particle distance for designing colorimetric chemosensors based on AgNPs and AuNPs. 20,22,30,31 In this regard, the aggregationdisaggregation approach has some drawbacks, including instability of bonded nanoparticles as well as unwanted effects of interferents in real samples. 32 There are also some compelling reasons for choosing AgNPs over AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…To address this need, colorimetric methods for detecting b-adrenergic agonists with acceptable selectivity and sensitivity standards have gained currency in recent years due to their low cost combined with the ease of visual inspection. [19][20][21][22][23][24] On top of these, the commercialization of colorimetric sensors can be more cost-effective than other methods. 25 Anisotropic noble metal nanoparticles of various forms and sizes have piqued the curiosity of scientists.…”
Section: Introductionmentioning
confidence: 99%